Upacara Pande Mbaru Gendang Di Kampung Tenda Kelurahan Tenda Kecamatan Langke Rembong Kabupaten Manggarai Flores Ntt - Sriyanti Kamis, Petronela; ., Purwadi; Murniasih, A.A. Ayu (Humanis; Vol 17 No 3 (2016), 2016)
Manggarai regency has numerous villages that preserve traditional ceremonies and Tenda Village, or Kampung Tenda becomes one of the villages that preserve the ceremony of Pande Mbaru Gendang. The aims of the study were to know the procession and procedures of the ceremony of Pande Mbaru Gendang and to know the meaning and function of the ceremony in Tenda Village. Theory of Robert K. Merton about manifest and latent functions was applied and the concept of the study talked about procession, ceremony, ceremony of Pande Mbaru Gendang, meaning, and function. Qualitative method was applied. The study showed there were three procedures in ceremony of Pande Mbaru Gendang. The first procedure was a ceremony before starting to build the traditional house; the second procedure was a ceremony in current progress of constructing traditional house; and the third procedure was a ceremony after finishing the traditional house. However, it was observed Pande Mbaru Gendang also experienced constant changes occurred in ceremonial procession of laying the first stone, Roko Molas Poco, and Congko Lokap. There were manifest and latent functions found in the ceremony of Pande Mbaru Gendang, and religious, education, kinship, and economic meanings were embodied in the ceremony.